VLSI design of low voltage digital signal processing (DSP) application using differential cascode voltage switch with pass-gate (DCVSPG) logic - 185875 They, Kian Seng (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2002